(untitled) (SAARC Journal of Agriculture, 2025)
The integrated financial service in agriculture is a relatively recent mechanism in increasing access to finance in different stages of agriculture production, processing, and marketing through an agriculture value chain approach (AVCF). This article examines how the AVCF contributes to rural development in terms of increased access to credit, market, and income stabilization. The aim is to evaluate the effectiveness of AVCF models in bridging the financing gap of smallholder farmers and agri-entrepreneurs, specifically through secondary data from developing nations. A qualitative review was made using the World Bank, FAO, IFAD reports, and the most recent literature. Key AVCF mechanisms such as contract farming, warehouse receipt systems, and out-grower schemes are analyzed. The findings indicate that AVCF has greatly influenced financial inclusion, rural employment, and agricultural productivity. But there are still obstacles, including policy restrictions, infrastructure weaknesses, and little financial knowledge. The research recommends scaling community forestry-VCF interventions within the context of enabling public-private partnerships is likely to accelerate rural change. SAARC J. Agric., 23(1): 224-236 (2025)